PERAN BAPEPAM SEBAGAI LEMBAGA PENGAWAS PASAR MODAL ATAS PELANGGARAN ADMINISTRASI KEGIATAN SHORT SELLING - sutomo sutomo (JURNAL ILMIAH LIVING LAW, 2015)
Stock market is a mean for those who have money and needs it for short, medium, and long investment. Although some legislation has been enacted, however there are still administrative violation concerning short selling stock market. Margin transaction is securities sales where the stocks are not owned by the seller at the time of transaction. Therefore, if something goes wrong or there are impersonating information, manipulation also fraud, could detriment the investors or the parties. To avoid these, an institution that holds maximum role and authority on behalf of Indonesia Capital Market supervisory board-financial institution (Bapepam-LK) is needed. This board aims to protect investors by managing law enforcement. One of the legal order that essentially needed to support economic development is the provision regulated in Legislation Number 8 of 1985 on Stock Market. This research is a descriptive analytical study while data collection performed by data reviewing which is obtained in the legislation, textbooks, journals, and prior research on the role of Bapepam as Capital Market Supervisory board on administrative on administrative violations of short selling activities.